Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pengguna Jasa Répondez S’il Vous Plait di Twogather Wedding Planner Bali - Ida Ayu Agung Adnyani Pidada; Ketut Arjaya; I Gusti Ayu Ratih Asmarani (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pariwisata Bali, 2022)
Events are not only carried out for business purposes but are also carried out for personal interests, one of which is wedding events. One of the wedding organizers working on the island of Bali is Twogather Wedding Planner Bali which can provide services for organizing wedding events such as catering, loudspeakers and RSVP. RSVP services are carried out to take into account the number of guests who come so this study was conducted to find out how the influence of the quality of services provided in the RSVP wedding on customer satisfaction at Twogather Wedding Planner Bali. This research was carried out with a quantitative approach using the method of multiple linear regression analysis. Questionnaires were distributed by accidental sampling to 34 respondents. The results of service quality research from reliability indicators, namely t-count in reliability (X1) amounted to 4,617 stating that service user satisfaction has a positive and significant effect on service quality, t- count in responsiveness (X2) amounted to 4,960 stating that service user satisfaction has a positive and significant effect on service quality, the t-count in the guarantee (X3) is 2.240 which states that service user satisfaction has a positive and significant effect on service quality, the t-count in empathy (X4) is -1.294 which states that service user satisfaction has a negative and insignificant effect on quality. service, t-count in empathy (X5) amounted to 7,832 states that service user satisfaction has a positive and significant effect on service quality